Analysis of interface states of the pentacene organic thin-film phototransistor by conductance technique - Okur, S.; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2009)
A pentacene thin-film transistor with a channel width of 300 mu m and a channel length of 30 mu m has been successfully fabricated on n-Si substrate with thermally oxidized SiO2 as a gate insulator. The photovoltaic and interface state density properties of the transistor have been investigated. A pentacene film of 200 nm thickness was deposited on the SiO2 layer with a vacuum thermal evaporator. Atomic force microscopy images of the pentacene film on SiO2 insulating layer show a homogeneous film surface with the rms roughness of I I run. The transistor shows p-channel characteristics, as a result of positive carriers generated in the pentacene film for the negative bias voltages applied to the gate. The photosensitivity (I-ph/I-dark) is measured as 1.45 at an illumination intensity of 3500 lux at the off state. This suggests that the pentacene thin-film transistor shows a phototransistor characteristic. The field-effect mobility of the pentacene OTFT was found to be 0.021 cm(2)/(V s). The interface state density of the transistor was determined using conductance technique and was found to be about 1.191 x 10(10)eV(-1) cm(-2). (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Organic semiconductor; Thin-film transistor; Interface state density